Inhibition of β-catenin protein expression by triptolide affects self-renewal of liver cancer stem cells - Zhou, Jian-Bo; Peng, Gang; Jia, Yu-Cheng; Li, Jun; Wang, Jia; Nie, Shu; Zhang, Qiu-Ying (Bangladesh Journal of Pharmacology, 2015)
The present study demonstrates the effects of triptolide, one of the constituents from Tripterygium wilfordii, on the self-renewal capacity of human hepatocellular carcinoma. The investigation revealed that triptolide markedly prevented the proliferation of liver cancer stem cells (LCSCs). For the LCSCs the minimum inhibitory concentration of triptolide was 0.6 ?M. There was a significant and obvious decrease in the capacity of LCSCs to form self-sphere. Furthermore, triptolide reduced the sphere-forming capacity of LCSCs along with inhibition of β-catenin expression. However, the exposure of triptolide-treated cells to lithium chloride, an activator the Wnt/β-catenin signaling pathway, reversed the triptolide-induced inhibition of β-catenin expression and inhibited the self-renewal capacity. Therefore, triptolide effectively eradicates LCSCs through the inhibition of β-catenin protein and may act as a novel agent for the treatment of hepatocellular carcinoma.